ANALYSIS OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION AT SURABAYA ORTHOPEDICS & TRAUMATOLOGY HOSPITAL - Tandiono, Teddy; Krisprimandoyo, Denpharanto Agung (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This study aims to analyse the influence of leadership style and work environment on employee performance which is mediated by job satisfaction at the Surabaya Orthopedic & Traumatology Hospital. The population in this study were employees at the Surabaya Orthopedic & Traumatology Hospital at lower levels, excluding medical and nursing personnel, so that included other health personnel, administrative personnel and non-health technical personnel. The sample in this study was 128 people consisting of 50 other health workers, 57 administrative staff and 21 non-health technical staff serving at the Surabaya Orthopedic & Traumatology Hospital. Primary data used in the research was obtained through a questionnaire. This research uses a Structural Equation Model with the Partial Least Square Method. The research results show that leadership style and work environment can have a direct and significant influence in a positive direction on employee performance. Apart from that, the variable job satisfaction can partially mediate the influence of leadership style and work environment on employee performance.